Effects of cardiac medications for patients with obstructive coronary artery disease by coronary computed tomographic angiography: Results from the multicenter CONFIRM registry. Issue 1 (January 2015) - Schulman-Marcus, Joshua; Hartaigh, Bríain ó; Giambrone, Ashley E.; Gransar, Heidi; Valenti, Valentina; Berman, Daniel S.; Budoff, Matthew J.; Achenbach, Stephan; Al-Mallah, Mouaz; Andreini, Daniele; Cademartiri, Filippo; Callister, Tracy Q.; et al.
Abstract Objective: This study sought to determine the correlation between baseline cardiac medications and cardiovascular outcomes in patients with obstructive coronary artery disease (CAD) diagnosed by coronary computed tomographic angiography (CCTA). Methods: 1637 patients (mean age 64.8 ± 10.2 years, 69.6% male) with obstructive CAD from the CONFIRM (COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter) registry were followed over the course of three years. Obstructive CAD was defined as a ≥50% stenosis in an epicardial vessel. Medications analyzed included statins, aspirin, beta-blockers, angiotensin converting enzyme (ACE) inhibitors, and angiotensin receptor blockers (ARBs). Using Cox proportional-hazards models, we calculated the hazard ratio (HR) with 95% confidence intervals (95% CIs) for incident major adverse cardiovascular events (MACE), defined as death, acute coronary syndrome, or myocardial infarction. Results: At the time of CCTA, 59%, 54%, 40%, and 46% of patients were using statins, aspirin, beta-blockers, and ACE inhibitors or ARBs, respectively. Statins were associated with a 43% (95% CI = 0.38–0.87, p = 0.008) lower adjusted risk of MACE. Following adjustment, aspirin, beta-blockers, ACE inhibitors and ARBs did not attenuate the risk of MACE. When restricted to patients with multivessel obstructive CAD, only statins were associated with lower risk of MACE. Conclusion: In patients with obstructive CAD by CCTA, the baseline use of statins was associated with improved clinical outcomes. Other cardiac medications—including aspirin, beta-blockers, ACE inhibitors, and ARBs—were not associated with reduced risk of MACE.